(untitled) (UNIZIK Journal of Educational Management and Policy, 2018)
The study investigated Nigerian recession aftermath: implications for the educational management of students in tertiary institutions. Two research questions and one hypothesis guided the study. Descriptive survey design was adopted. 106 students were sampled from the 534 final year students in the nine departments, Faculty of Education Nnamdi Azikiwe University, Awka. Simple random sampling technique was employed to obtain 20% of the respondents from each department. The instrument for data collection was a questionnaire. The validation of the instrument was done by experts in Educational Management and Policy Department and an expert in Measurement and Evaluation in Educational Foundations Department of Nnamdi Azikiwe University, Awka. Cronbach alpha was used to determine the reliability of the instrument. This yielded reliability co-efficient of 0.85. Data obtained were analyzed through mean and t-test statistic. Findings of the study indicate that, educational management services are poorly provided in tertiary institutions due to recession aftermath. Also, dearth of funds affects the educational management of students in tertiary institutions. Based on the findings, the study recommends among others that, prioritizing adequate budgetary allocation and making adequate provisions for educational management of tertiary students by the government is imperative and apt.